Internet addiction and depressive symptoms: a dose-response effect mediated by levels of physical activity - Lauro Miranda Demenech; Marlos Rodrigues Domingues; Rosângela Mattos Muller; Vera Regina Levien; Samuel Carvalho Dumith (Trends in Psychiatry and Psychotherapy, 2023)
Abstract Introduction There are several negative impacts on the physical and mental health of people presenting internet addiction, including development of mood disorders, such as depression. Objective The aim of the study was to evaluate the association between internet addiction and depressive symptoms, as well as to test the mediating role of physical activity in this association. Methods A cross-sectional study was conducted with undergraduate students from three universities (one private and two public institutions) in southern Brazil. Depressive symptoms were measured with the Beck Depression Inventory (BDI-21), internet addiction with the Internet Addiction Test (IAT-20), and physical activity with the International Physical Activity Questionnaire (IPAQ – short version). Poisson regression and the Karlson-Holm-Breen mediation method were used for statistical analyses. Results We observed a dose-response relationship between internet addiction and depressive symptoms. Levels of physical activity mediated the association between moderate internet addiction and depressive symptoms, accounting for 10.7% of the effect observed. Conclusion Internet addiction can be detrimental to individuals’ health, contributing to development of depressive symptoms. Along with psychological and pharmacological therapies, prescription of physical activities is recommended.